ANALISIS EFEKTIVITAS BAURAN PROMOSI PADA KONSUMEN LIBRA MOTOR BATUSANGKAR (Studi Pada Pengguna Motor Metic Merek Honda Batu Sangkar) - Raudatul Nurjannah; Bambang Munas Dwiayanto (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to (1) identify consumer characteristics, (2) identify promotion mix, (3) analyze promotion effectiveness at the Batusangkar Libra Motor Company. This research uses descriptive quantitative analysis, EPIC Model, and Direct Rating Method with the help of SPSS software version 25.0. The results of the study: Promotional variables through advertising are within the range of a fairly effective scale, namely at 3.22. Direct Rating Ads score in a good promotion position, which is 69.52. Interactive Marketing on a fairly effective scale of 3.00. The Interactive Marketing direct Rating score is in a good position, namely 78.84. Meanwhile, the Sales Promotion was declared effective, namely 3.89. The direct rating score for Sales Promotion through joint events and community promos is in a good promotional position, namely 73.56.